Secondary two normal academic mathematics model examination papers (Singapore : Educational Publishing House, 2014)
Secondary 2 Normal (Academic) Mathematics Model Examination Papers is written in accordance with the latest MOE Secondary Mathematics Syllabus. This book contains 8 sets of examination papers to help students in preparing for their examinations. Questions in this book are specially crafted to test students' knowledge and their ability to apply mathematical concepts in answering the questions. This book aims to help students in mastering problem solving skills and boost their confidence in tackling questions in their school examinations.
Keywords: Mathematics--Examinations--Periodicals.